THE INFLUENCE OF SPRAWL DEVELOPMENT, INCOME, AND INFRASTRUCTURE ON ENERGY CONSUMPTION IN CENTRAL JAVA PROVINCE, INDONESIA - Imam Buchori; Angrenggani Pramitasari; Agung Sugiri; Anang Wahyu Sejati; Maryono Maryono; Yudi Basuki (Geoplanning: Journal of Geomatics and Planning, 2018)
Energy consumption is influenced by many factors. Sprawl development is often alleged as one of its driving factors. Other factors like the increase of community welfare and the improvement of regional infrastructures are often indicated to trigger energy consumption. This study is aimed at investigating the influence of sprawl development and other relevant factors on the energy consumption in Central Java Province, Indonesia. Other variables denoted to influence energy consumption used in this study are road density, people’s income represented by local Gross Domestic Product (GDP) per capita, and GDP growth rate. The observed energy is limited on vehicle fuels. After investigating the significance of correlations among variables, a multiple regression model is employed. By eliminating GDP per capita because of its multicollinearity with other dependent variables, the developed formula shows that fuel consumption is generated by 47.84 of sprawling index, added by 17.21 of road ratio and 17.5 of GDP growth rata, and reduced by a constant of 26.18. These measurements are expected to be useful for urban and regional managers in developing their region, especially in estimating the fuels’ consumption considering the determined regional policies.